Sequential implant strategies with Synovex-S® and trenbolone acetate-containing implants in calf-fed Holstein steers - D.D. Simms; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1993)
In a commercial feedyard trial, 242 Holstein steer calves averaging 378 lb were used to compare effects of six alternative implant programs, consisting of sequential use of Synovex-S® or a combination of estradiol and trenbolone acetate (Revalor-S® or Finaplix- S® plus Synovex-S®), on feedlot performance and carcass characteristics. The calves were implanted three times at 78- to 90-day intervals while on feed an average of 252 days. The combination implant increased (P<.05) gain by .13 to .21 lb per day in all three implant periods compared to Synovex alone. Total feedlot gain was increased in direct relation to the number of times steers received the combination implant. However, marbling score and the percentage of carcasses grading USDA Choice tended to be reduced with repeated use of Revalor or Finaplix.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Revalor; Trenbolone acetate; Finishing; Holsteins; Carcass traits